2010
DOI: 10.1074/jbc.m110.125534
|View full text |Cite
|
Sign up to set email alerts
|

CCK1 and CCK2 Receptors Are Expressed on Pancreatic Stellate Cells and Induce Collagen Production

Abstract: The gastrointestinal hormone cholecystokinin (CCK) can induce acute pancreatitis in rodents through its action on acinar cells. Treatment with CCK, in combination with other agents, represents the most commonly used model to induce experimental chronic pancreatitis. Pancreatic stellate cells (PSC) are responsible for pancreatic fibrosis and therefore play a predominant role in the genesis of chronic pancreatitis. However, it is not known whether PSC express CCK receptors. Using real time PCR techniques, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 50 publications
4
60
0
Order By: Relevance
“…On day 2, the culture inserts were placed into 6-well plates containing Panc-1 cells (0.8 × 10 6 cells/well), followed by treatment with ORM (10 µM) and GEM (100 nM) and incubated up to 2 days in DMEM medium. As previous studies have shown TGF-β to be a potent inducer of epithelial-mesenchymal transition (EMT) in several cancer cells including pancreatic cancer cells (26, 27), we used recombinant TGF-β (2 ng/ml) to stimulate the stromal cells as a mediator of PSC-induced EMT in cells.…”
Section: Methodsmentioning
confidence: 99%
“…On day 2, the culture inserts were placed into 6-well plates containing Panc-1 cells (0.8 × 10 6 cells/well), followed by treatment with ORM (10 µM) and GEM (100 nM) and incubated up to 2 days in DMEM medium. As previous studies have shown TGF-β to be a potent inducer of epithelial-mesenchymal transition (EMT) in several cancer cells including pancreatic cancer cells (26, 27), we used recombinant TGF-β (2 ng/ml) to stimulate the stromal cells as a mediator of PSC-induced EMT in cells.…”
Section: Methodsmentioning
confidence: 99%
“…An additional role in exocrine function has been demonstrated, whereby the gastrointestinal hormone cholecystokinin (CCK) induces acetylcholine secretion by PaSCs, which in turn stimulates amylase secretion by acinar cells [20]. Furthermore CCK has been shown to have direct activating effect on PaSCs, and induces collagen synthesis [21].…”
Section: Pancreatic Stellate Cellsmentioning
confidence: 98%
“…21 CCK receptors have also been identified on pancreatic stellate cells and when stimulated with CCK, these cells produce collagen. 22,23 Therefore, it has been proposed that CCK plays an important role in pancreatic carcinogenesis and the fibrosis associated with pancreatic cancer. 24 …”
Section: Introductionmentioning
confidence: 99%